The Evolution of Modern Trends in Education Quality Management - N.K., Dyusheeva; M.D., Choguldurov; R.A., Kutanova; K.K., Kadyrkulov; M.Z., Asanbaev (Journal of Ecohumanism, 2025)
Education quality management has undergone significant transformations in recent decades, influenced by global demands, technological advancements, and changing educational paradigms. This research paper explores the evolution of modern trends in education quality management (EQM), focusing on the key drivers that have shaped its development. Initially, education systems were designed with a traditional, teacher-centered approach, but the need for more dynamic, student-centered learning environments led to the introduction of quality assurance (QA) mechanisms such as accreditation, performance-based assessments, and standards-setting initiatives. The paper examines how the rise of digital tools, data analytics, and artificial intelligence (AI) has enabled more personalized learning experiences and real-time tracking of educational outcomes. Furthermore, the shift towards inclusivity and the recognition of diverse learner needs have prompted educational institutions to adopt more flexible and adaptive systems for quality management. In addition, globalization has encouraged cross-border collaborations, resulting in the development of international frameworks and best practices for maintaining educational standards. By reviewing contemporary models, including Total Quality Management (TQM) and Six Sigma, the paper assesses how EQM has become increasingly focused on continuous improvement and stakeholder engagement. The research also discusses the challenges and opportunities posed by current trends, including the integration of sustainability goals and the importance of preparing students for a rapidly evolving workforce. Ultimately, this paper highlights the importance of adapting education quality management to meet the evolving demands of society and the global economy, ensuring that education remains accessible, equitable, and of the highest possible standard.